Antioxidant, toxicity and proximate analysis of archidendron pauciflorum (Jering) / Mohd Khairi Ishak - Ishak, Mohd Khairi (2017)
A research has being conducted on Archidendron pauciflorum obtained from argo market at Kuala Pilah. The study aim is to determine the presence of antioxidant properties of Archidendron pauciflorum by using DPPH assay, which potentially can be used in pharmaceutical and human health. The samples were extracted by using sonicator. The explant such as seeds and pods were screening for antioxidant activity. The highest percentage of scavenging activity was showed by seeds (91.87%) followed by pods (85%). Then, these two samples were further tested to investigate the toxicity level of Archidendron pauciflorum by using brine shrimp lethality assay and also determination of lethal concentration LC50 as a standard toxicity indicator. Explant that showed highest lethal concentration LC50 effected in 24 hours was seeds (1.944 mg/ml) followed by pods (1.884 mg/ml). This two sample showed low toxicity level since the lethal concentration was higher than 1 mg/ml. This study showed that explant might become potential sources since as it has high antioxidant with low toxicity level. Then, these two were continues study to determine the proximate analysis. Explant that showed the higher carbohydrate and protein was seeds (84.45%) and (3.33%) while pods (76.84%) and (2.03%). But seeds were lower in moisture, ash and fat content (8.85%), (3.17%) and (0.20%) compared to pod (10.67%), (10.23%) and (0.23%). This study showed that explant also might become the potential to produce healthy snack since it has high carbohydrate and protein content.